Inhibition of DNA Methylation at the MLH1 Promoter Region Using Pyrrole–Imidazole Polyamide - Shinohara, Ken-ichi (ACS Omega, 2016)
[Image: see text] Aberrant DNA methylation causes major epigenetic changes and has been implicated in cancer following the inactivation of tumor suppressor genes by hypermethylation of promoter CpG islands. Although methylated DNA regions can be randomly demethylated by 5-azacytidine and 5-aza-2′-deoxycytidine, site-specific inhibition of DNA methylation, for example, in the promoter region of a specific gene, has yet to be technically achieved. Hairpin pyrrole (Py)–imidazole (Im) polyamides are small molecules that can be designed to recognize and bind to particular DNA sequences. In this study, we synthesized the hairpin polyamide MLH1_–16 (Py-Im-β-Im-Im-Py-γ-Im-Py-β-Im-Py-Py) to target a CpG site 16 bp upstream of the transcription start site of the human MLH1 gene. MLH1 is known to be frequently silenced by promoter hypermethylation, causing microsatellite instability and a hypermutation phenotype in cancer. We show that MLH1_–16 binds to the target site and that CpG methylation around the binding site is selectively inhibited in vitro. MLH1_non, which does not have a recognition site in the MLH1 promoter, neither binds to the sequence nor inhibits DNA methylation in the region. When MLH1_–16 was used to treat RKO human colorectal cancer cells in a remethylating system involving the MLH1 promoter under hypoxic conditions (1% O(2)), methylation of the MLH1 promoter was inhibited in the region surrounding the compound binding site. Silencing of the MLH1 expression was also inhibited. Promoter methylation and silencing of MLH1 were not inhibited when MLH1_non was added. These results indicate that Py–Im polyamides can act as sequence-specific antagonists of CpG methylation in living cells.